Analysis of Community Behavior Change Strategy in Open Defecation Behavior in the Work Area of Yembekiri Health Center, Teluk Wondama Regency, West Papua - Herlinda Sesa Rinding; Astrid Novita (Jurnal EduHealth, 2024)
The practice of open defecation is still a serious public health problem in many areas in Indonesia, including in the Yembekiri Health Center Work Area, Teluk Wondama Regency, West Papua. This study aims to analyze strategies for changing community behavior in the practice of open defecation in the area. The research design used was qualitative research. Data collection techniques were carried out randomly by means of in-depth interviews, observation checklists and document review checklists. The sample used in this study were 2 Yembekiri Health Center officers and 70 people who would be used as informants in this study. Results: Context; healthy toilets, clean water facilities are not yet effective because healthy facilities / toilets are still lacking in the Yembekiri Health Center work area as well as clean water facilities do not meet the needs of the local community. input component; inadequate community human resources, facilities and infrastructure are not yet effective The lack of toilets in various villages is the main complaint of the community even though clean water facilities are still sufficient and so in various other villages there are private toilets but clean water facilities are lacking so that people prefer to defecate on the beach. Process Component; Environmental pollution is still a problem in the work area of ​​Yembekiri Health Center. Open Defecation Behavior has become a habit of the community, especially children. The emergence of disease outbreaks, the scope of diarrhea cases is the most common case found in the work area of ​​Yembekiri Health Center after cases of ARI and malaria.